What does it take to be a star? The role of performance and the media for German soccer players - Erik E. Lehmann; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2007)
We test existing superstar theories for the German soccer league. We use various measures for individual players' performance and media presence to analyze whether performance and popularity can explain salaries and superstars in soccer. Moreover, we argue that quantile regression technique should be applied to analyze superstar phenomena instead of OLS used hitherto.
Keywords: J3; J4; L83; Z1; 330; superstars; soccer; quantile regressions; Rosen; Adler; Lohnniveau; Werbewirkung; Sportler; Fußballsport; Schätzung; Deutschland